2022
DOI: 10.3390/mi13040617
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Nitrogen-Doping Effect on Sub-Gap Density of States in a-IGZO TFTs by TCAD Simulation

Abstract: In this work, the impact of nitrogen doping (N-doping) on the distribution of sub-gap states in amorphous InGaZnO (a-IGZO) thin-film transistors (TFTs) is qualitatively analyzed by technology computer-aided design (TCAD) simulation. According to the experimental characteristics, the numerical simulation results reveal that the interface trap states, bulk tail states, and deep-level sub-gap defect states originating from oxygen-vacancy- (Vo) related defects can be suppressed by an appropriate amount of N dopant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…This is well-matched with the XPS results. According to previous reports, mechanical stress may weaken the bonding of the oxide semiconductor (ex, a-IGZO) and form the various defects. ,, Typical oxygen-related defects, oxygen vacancies (V o ), exist in neutral (V o 0 ) or two positive charge states (V o 2+ ) and correspond to N GA and N GD , respectively. In addition, the formation energy of V o 2+ is lower than that of V o 0 under outward displacement. , Through the TCAD simulation, it was confirmed that SS deteriorated regardless of elongation direction due to increased defects ( N GA and N GD ) in the IGZO channel layer after repeated mechanical stress. Therefore, the oxygen-vacancy-related defect change of the oxide semiconductor due to repeated mechanical stress is shown in Figure (c).…”
Section: Resultsmentioning
confidence: 78%
“…This is well-matched with the XPS results. According to previous reports, mechanical stress may weaken the bonding of the oxide semiconductor (ex, a-IGZO) and form the various defects. ,, Typical oxygen-related defects, oxygen vacancies (V o ), exist in neutral (V o 0 ) or two positive charge states (V o 2+ ) and correspond to N GA and N GD , respectively. In addition, the formation energy of V o 2+ is lower than that of V o 0 under outward displacement. , Through the TCAD simulation, it was confirmed that SS deteriorated regardless of elongation direction due to increased defects ( N GA and N GD ) in the IGZO channel layer after repeated mechanical stress. Therefore, the oxygen-vacancy-related defect change of the oxide semiconductor due to repeated mechanical stress is shown in Figure (c).…”
Section: Resultsmentioning
confidence: 78%
“…Based on the XPS spectra of the In 3d 5/2 , Ga 2p 3/2 , and Zn 2p 3/2 peaks presented in Figure S1, it was found that the increase in O def resulted from the dissociation of the In–O and Zn–O bonds. Oxygen vacancies (V O ) can exist as 2+ charged V O (V O 2+ ) and neutral V O (V O 0 ), and these species are located in the CBM and VBM, respectively. Therefore, to verify the increase in O def of a-IGZO in the stacked films after the annealing at 600 °C, we examined sub-gap states using SE and XPS valence band edge. Figure c shows the variations in the SE and XPS valence band spectra of a-IGZO in the stacked film, and the inset in the SE spectra shows the E opt of a-IGZO.…”
Section: Resultsmentioning
confidence: 99%
“…A new type of defect in the oxide semiconductor could be formed by its interaction with PI, such as fluorine, nitrogen, etc. 28,33 These interface charge trappings and scatterings can result in a degradation in the device's performance. Use of Al 2 O 3 in the interface region as an interlayer could prevent the formation of interface trap sites because Al 2 O 3 has a large band gap (∼6.0 eV) and high binding energy (metal−oxygen).…”
Section: Introductionmentioning
confidence: 99%
“…The existing flexible substrate is not suitable for the current semiconductor fabrication process, which involves high temperatures for the Ox-TFT. , Inorganic GIs have high tensile strength to crack with bending or stretching tests and have a high-temperature fabrication process. , Therefore, to achieve a high-mobility flexible device, we used an oxide semiconductor with low-temperature deposition conditions and PI as a gate insulator by optimizing of the fabrication process for the flexible device with an aluminum oxide (Al 2 O 3 ) interlayer. A new type of defect in the oxide semiconductor could be formed by its interaction with PI, such as fluorine, nitrogen, etc. , These interface charge trappings and scatterings can result in a degradation in the device’s performance. Use of Al 2 O 3 in the interface region as an interlayer could prevent the formation of interface trap sites because Al 2 O 3 has a large band gap (∼6.0 eV) and high binding energy (metal–oxygen).…”
Section: Introductionmentioning
confidence: 99%